Association of Midlife Hypertension with Late‐Life Hearing Loss. (6th August 2019) - Reed, Nicholas S.; Huddle, Matthew G.; Betz, Joshua; Power, Melinda C.; Pankow, James S.; Gottesman, Rebecca; Richey Sharrett, A.; Mosley, Thomas H.; Lin, Frank R.; Deal, Jennifer A.
Abstract : Objective: To investigate the association of midlife hypertension with late‐life hearing impairment. Study Design: Data from the Atherosclerosis Risk in Communities study, an ongoing prospective longitudinal population‐based study (baseline, 1987‐1989). Setting: Washington County, Maryland, research field site. Subjects and Methods: Subjects included 248 community‐dwelling men and women aged 67 to 89 years in 2013. Systolic blood pressure (SBP) and diastolic blood pressure were measured at each of 5 study visits from 1987‐1989 to 2013. Hypertension was defined by elevated systolic or diastolic blood pressure or antihypertensive medication use. A 4‐frequency (0.5‐4 kHz) better‐hearing ear pure tone average in decibels hearing loss (dB HL) was calculated from pure tone audiometry measured in 2013. A cutoff of 40 dB HL was used to indicate clinically significant moderate to severe hearing impairment. Hearing thresholds at 5 frequencies (0.5‐8 kHz) were also considered separately. Results: Forty‐seven participants (19%) had hypertension at baseline (1987‐1989), as opposed to 183 (74%) in 2013. The SBP association with late‐life pure tone average differed by the time of measurement, with SBP measured at earlier visits associated with poorer hearing; the difference in pure tone average per 10–mm Hg SBP measured was 1.43 dB HL (95% CI, 0.32‐2.53) at baseline versus −0.43 dB HL (95% CI, −1.41 to 0.55) in 2013. Baseline hypertension was associated with higher thresholds (poorer hearing) at 4 frequencies (1, 2, 4, 8 kHz). Conclusion: Midlife SBP was associated with poorer hearing measured 25 years later. Further analysis into the longitudinal relationship between hypertension and hearing impairment is warranted.